A tunable bandstop filter using triangular patch resonator with defected ground structures. Issue 12 (22nd September 2016) - Pinheiro, J.M.; Serrano, A.L.C.
ABSTRACT: A tunable dual‐mode bandstop patch filter with two degrees of liberty controlling the filter's central frequency and bandwidth is presented. The bandstop filter uses a single triangular resonator miniaturized by two slots and two defected ground structures (DGSs) slots to improve rejection. Varactor diodes are used across the patch's slots to vary the frequency of each degenerate fundamental mode. The models used in simulations, varactors assembling, DC bias configuration and measured results are presented. The proposed filter presents 17% of center frequency tuning range in the 5.8 GHz WiMAX band and the fractional bandwidth can be varied from 1.8% to 18%. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2930–2933, 2016